Efficacy and safety of PD-1/PD-L1 inhibitors in advanced or recurrent endometrial cancer: a meta-analysis with trial sequential analysis of randomized controlled trials - Ji Ren; Jinghe Wang; Yanan Wang; Dongying Yang; Jianming Sheng; Shili Zhu; Yunli Liu; Xiaoqi Li; Wei Liu; Binbin Zhang (Frontiers in Immunology)
BackgroundThe combination of programmed cell death 1 (PD-1)/programmed death ligand 1 (PD-L1) inhibitors with chemotherapy (CT) is currently under evaluation as a first-line treatment for advanced or recurrent endometrial cancer (EC). This study sought to assess the efficacy and safety of this therapeutic combination in patients with advanced or recurrent EC.MethodsWe performed an exhaustive review of randomized controlled trials (RCTs) up to September 25, 2024, examining the efficacy and safety of combining PD-1/PD-L1 inhibitors with CT versus CT alone (or plus placebo) in advanced or recurrent EC. Efficacy was measured by progression-free survival (PFS) and overall survival (OS), while safety was assessed by the incidence of any grade or grade ≥ 3 adverse events (AEs). We calculated hazard ratios (HRs) for PFS and OS, as well as risk ratios (RRs) for AEs, each accompanied by 95% confidence intervals (CIs). To evaluate heterogeneity, we employed Cochran’s Q test, I2 statistics, and 95% prediction intervals (PIs). Trial sequential analysis (TSA) was conducted using R Version 4.3.1, STATA Version 12.0, and TSA Version 0.9.5.10 Beta software.ResultsOur analysis incorporated 6 studies, encompassing a total of 2,954 patients. The combination of PD-1/PD-L1 inhibitors with CT significantly improved PFS (HR = 0.617, 95% CI: 0.506-0.752; 95% PI: 0.334-1.140) and OS (HR = 0.774, 95% CI: 0.664-0.902; 95% PI: 0.553-1.083) compared to CT alone (or plus placebo) in the overall population. Subgroup analysis based on mismatch repair (MMR) status revealed pronounced benefits in PFS and OS for patients with deficient MMR (dMMR) (PFS: HR = 0.344, 95% CI: 0.269-0.438; 95% PI: 0.231-0.510; OS: HR = 0.371, 95% CI: 0.245-0.562; 95% PI: 0.025-5.461) compared to those with proficient MMR (pMMR) (PFS: HR = 0.772, 95% CI: 0.627-0.950; 95% PI: 0.394-1.512; OS: HR = 0.996, 95% CI: 0.692-1.435; 95% PI: 0.021-47.662). Although there was no observed difference in the incidence of any grades AEs (RR = 0.994, 95% CI: 0.982-1.006; 95% PI: 0.978-1.009), the risk of grade ≥ 3 AEs was elevated in the group receiving PD-1/PD-L1 inhibitors in combination with CT (RR = 1.132, 95% CI: 1.023-1.252; 95% PI: 0.836-1.532).ConclusionThe combination of PD-1/PD-L1 inhibitors with CT significantly improved PFS and OS in advanced or recurrent EC patients, with particularly pronounced benefits observed in those with dMMR. Clinicians can tailor treatment strategies according to individual patient characteristics to optimize therapeutic outcomes, while remaining alert to the possibility of AEs in clinical practice.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024595455.